2019
DOI: 10.1021/acsphotonics.9b00185
|View full text |Cite
|
Sign up to set email alerts
|

Organic Monolithic Natural Hyperbolic Material

Abstract: Materials with hyperbolic dispersion are the key to a variety of photonic applications involving nanoimaging, hyper-lensing, and spontaneous emission engineering, due to the availability of high k modes. Here we demonstrate that spin-coated polycrystalline organic semiconducting films with a layered molecular packing structure can exhibit a hyperbolic dispersion over a wide spectral range and support the presence of surface excitonic polaritons. This was evidenced from 670 to 920 nm and is related to the negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…1a. The ideal HMM has an unlimited k-space, while a practical HMM, made by Ag-SiO 2 multilayer, has a k-space limitation from its periodicity [23][24][25][26] . A multilayer with a smaller period of alternating layers supports a higher spatial frequency.…”
Section: Resultsmentioning
confidence: 99%
“…1a. The ideal HMM has an unlimited k-space, while a practical HMM, made by Ag-SiO 2 multilayer, has a k-space limitation from its periodicity [23][24][25][26] . A multilayer with a smaller period of alternating layers supports a higher spatial frequency.…”
Section: Resultsmentioning
confidence: 99%
“…Herein, we demonstrate an unprecedented fluorophore photostability enabled by a self‐assembled organic hyperbolic material (OHM) film [ 28 ] in the visible spectrum. Compared to traditional HMMs [ 22,29,30 ] made of noble metal structures and other natural hyperbolic materials, [ 31–33 ] the OHMs used in this work feature a Lorentz‐type dispersion [ 33,34 ] with low‐loss natural hyperbolic polariton modes, [ 28 ] and thus support an extremely large LDOS and a large Purcell factor. [ 35 ] Moreover, this low‐loss hyperbolic nature of the OHM films also makes an efficient fluorescence enhancement without any outcoupling structure possible.…”
Section: Figurementioning
confidence: 99%
“…For Ag, the resonance peak wavelength is centered around 440 nm, [ 39 ] and for Au it is centered at 620 nm. [ 40–42 ] TiN‐based HMMs, [ 43,44 ] Ag‐based HMMs, [ 20,21,23,33,45–50 ] and Au‐based HMMs [ 40,51,52 ] support a broadband but relatively small PF. The OHMs used in this work provide PFs two orders of magnitude larger than the values found in those plasmonic materials, and even comparable to the values attained by using plasmonic nanostructures such as nanoantennae, [ 11,41 ] nanocavities, [ 53 ] and nanogratings [ 21,48 ] in the spectral range of 480–560 nm.…”
Section: Figurementioning
confidence: 99%
“…An important challenge which must be overcome to fully exploit the useful properties of naturally hyperbolic media is the development of low-loss, practical hyperbolic materials at visible frequencies. Recent studies of organic films made by the solution-processing method have shown strong Lorentz-type optical dispersions including a negative real part of permittivity from molecular conformation and strong inter-molecular interactions [30][31][32] . In the case that a transition's oscillator strength is sufficiently large, the maximal Im(ε) 1, Re(ε) can become negative.…”
mentioning
confidence: 99%
“…In the case that a transition's oscillator strength is sufficiently large, the maximal Im(ε) 1, Re(ε) can become negative. Since Im(ε) decays faster than Re(ε), as frequency is tuned away from resonance, there can exist an off-resonance frequency range over which Re(ε) is negative and Im(ε) is small [30][31][32] . Thus, organic films exhibiting these specific optical properties are likely to be attractive substitutes for metals at visible frequencies.…”
mentioning
confidence: 99%